Reduction of inorganic phosphorus levels in broiler rations - Cruz, Frank George Guimarães (2014)
Cobb broilers were fed until 56 days of age, to verify the effects of P levels in four treatments constituted of T1 = 100% of the N.R.C. recommendations for total P, T2 = 95%, T3 = 90% and T4 = 85%, on the starting (1-21 days), growing (22-42 days) and finishing (42-56 days) phases, respectively. The following parameters were evaluated: feed intake, weight gain, feed conversion and blood P level. After the broilers were slaughtered (56 days), tibia breaking resistance was evaluated. Calcium and phosphorus from the ashes of the tibia were also determined. Analysis of variance of the data was performed and the differences were compared by Duncan's test. The results allow to condude that for the starting phase (1-21 days) the total P level recommended would be equal to 0.75% (100% N.R.Cj.); for the growing phase (22-42 days) the best performance was obtained with the level of 0.66% (95% N.R.C.), and for the finishing phase (43-56 days) the levels of 0.61% and 0.57% (95% and 90% N.R.C.) presented similar results as to the feed conversion and cost of productionfor a unit of gain.